Neuroprotective effects of erythropoietin against hypoxic injury via modulation of the mitogen-activated protein kinase pathway and apoptosis - Ji Eun Jeong; Jae Hyun Park; Chun Soo Kim; Sang Lak Lee; Hai Lee Chung; Woo Taek Kim; Eun Joo Lee (Korean Pediatric Society, 2017)
PurposeHypoxic-ischemic encephalopathy is a significant cause of neonatal morbidity and mortality. Erythropoietin (EPO) is emerging as a therapeutic candidate for neuroprotection. Therefore, this study was designed to determine the neuroprotective role of recombinant human EPO (rHuEPO) and the possible mechanisms by which mitogen-activated protein kinase (MAPK) signaling pathway including extracellular signal-regulated kinase (ERK1/2), JNK, and p38 MAPK is modulated in cultured cortical neuronal cells and astrocytes.MethodsPrimary neuronal cells and astrocytes were prepared from cortices of ICR mouse embryos and divided into the normoxic, hypoxia (H), and hypoxia-pretreated with EPO (H+EPO) groups. The phosphorylation of MAPK pathway was quantified using western blot, and the apoptosis was assessed by caspase-3 measurement and terminal deoxynucleotidyl transferase dUTP nick end labeling assay.ResultsAll MAPK pathway signals were activated by hypoxia in the neuronal cells and astrocytes (P<0.05). In the neuronal cells, phosphorylation of ERK-1/-2 and apoptosis were significantly decreased in the H+EPO group at 15 hours after hypoxia (P<0.05). In the astrocytes, phosphorylation of ERK-1/-2, p38 MAPK, and apoptosis was reduced in the H+EPO group at 15 hours after hypoxia (P<0.05).ConclusionPretreatment with rHuEPO exerts neuroprotective effects against hypoxic injury reducing apoptosis by caspase-dependent mechanisms. Pathologic, persistent ERK activation after hypoxic injury may be attenuateed by pretreatment with EPO supporting that EPO may regulate apoptosis by affecting ERK pathways.